Justified corrections to avian names under Article 32.5.1.1 of the International Code of Zoological Nomenclature - David, Normand; Dickinson, Edward C.; Gregory, Steven M. S. (Zootaxa, 2009)
Various avian names are examined in the context of Art. 32.5.1.1, a clause newly introduced in the 1999 Code, which applies retroactively; this permits clear decisions in 21 cases where qualifying corrigenda exist. In addition, we detail three names having dual original spellings, but that were not addressed by a First Reviser or in a corrigendum; they are provided as background, but they too should be captured in any planned database for actions under Art. 32.5